Effect of spirulina microalgae biodiesel enriched with diesel fuel on performance and emission characteristics of CI engine. (15th May 2020) - Rajak, Upendra; Nashine, Prerana; Verma, Tikendra Nath
Graphical abstract: Highlights: Engine performance suffers slightly with addition spirulina microalgae to diesel. NOX trade-off can be overcome with suitable spirulina microalgae and its blends. The smoke and PM emission is reduced using spirulina biodiesel compared to diesel. Abstract: This research, the effects of the spirulina microalgae biodiesel (SMB) blends containing 20, 40, 60 and 80% in volume based were investigated in a naturally aspirated diesel engine at various loads. The performance, combustion and emission analyses showed that of the injection timings (23.0° b TDC) with higher injection pressure of 220 bar. The results show that SMB1 (20% of spirulina microalgae biodiesel and 80% diesel) produces lower exhaust emission and cylinder pressures, brake thermal efficiency (BTE), exhaust temperature and maximum rise pressure rates as compared to diesel fuel. Specific fuel consumption and ignition delay period results increased up to 3.3%, 8.2% and BTE reduced up to 3.03% when the spirulina microalgae blend was increased to 20% at the higher load. The SMB blends also resulted in lower nitrogen oxides (NOX ) emission by 4.9%, particulate matter (PM) emission by 20.7% as well as lower smoke by 5.4%, but CO2 emissions increased for all loads. The results showed that addition spirulina microalgae produced a lower of brake thermal efficiency and exhaust temperature, the CO2 emission were improved. Hence, spirulina microalgae can be used in diesel engine.